Revista Raça Brasil: negros em movimento (1996-2004) - Nicolini, Veridiana Kunzler (2007)
This dissertation intends to analyze "Raça Brasil" (Brazilian Race) Magazine, aimed to the colored people. It will be used, as information base for this study, the above mentioned magazine and some issues of the press, previous to this magazine first edition, to evidence the evolution that the editorials have experienced regarding this matter, and the relations set up among the magazine and other communications means, such as television, electronic media and publicity. Through the magazine study it is also appraised the colored people social fight against prejudice, the relation between the organized colored people movements and the way "Raça Brasil" is engaged in this process